ANALISIS TINGKAT KEMANDIRIAN DAN KINERJA KEUANGAN DAERAH DAN HUBUNGANNYA DENGAN BELANJA MODAL PROVINSI JAMBI 2001 - 2012 - . Rafniati; Tona Aurora L; Fitrini Mansur (Magister Ilmu Akuntansi Universitas Jambi, 2016)
The study entitled An Analysis of Regional Desentralization level and Financial Performance, and it’s Correlation toward Capital Expenditure of Jambi Province 2001-2012. There are three aims of this thesis, they are : first, to analyze the regional desentralization level of Jambi Province ; second, to analyze the financial performance of Jambi Province ; third, to analyze the correlation between desentralization level and financial performance toward capital expenditure of Jambi Province 2001-2012. Due to the methodelogy of research, this thesis used descriptive quantitative method within 3 research instruments ; the regional desentralization rasio, financial performance rasio and corelation. The result of this research has concluded that first, the level of regional desentralization level of Jambi Province was in sufficient category. Second the regional financial performance of Jambi performance was in very effective category, however inefficient. Meanwhile the level of regional tax effort was still low. Third, it was found that there was no significant corelation between regional desentralization level and regional financial performance.